IMPLEMENTASI AKAD QARDH PADA PENYEDIAAN BENIH JAGUNG BAGI PETANI DALAM PERSPEKTIF ETIKA EKONOMI ISLAM - Siswoyo; Moch Syifa'ul Fu'ad (Program Studi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Nahdlatul Ulama Tuban, 2026)
Limited capital at the start of the planting season is a major obstacle maize farmers face when acquiring seeds. One financing option aligned with Sharia principles is the qardh agreement a loan arrangement that entails no additional charges. This study aims to analyze the implementation of the qardh agreement for maize seed provision at Toko Suroso Berkah in Sembung Village and to examine its alignment with Islamic economic ethics. A qualitative approach utilizing phenomenology was employed. Data were gathered through observation, in-depth interviews, and document collection, then analyzed using an interactive analysis techniqueinvolving data reduction, information presentation, and conclusion drawing alongside source triangulation to verify accuracy. The findings indicate that the qardh agreement is implemented by providing seeds to farmers without upfront payment; repayment occurs post-harvest and is free from interest, penalties, or additional fees. This mechanism helps overcome capital constraints, sustains farming operations, boosts productivity, and strengthens the partnership and trust between the shop owner and the farmers. From the perspective of Islamic economic ethics, the practice reflects values ??such as ta'awun (mutual assistance), amanah (trustworthiness), justice, and maslahah (public interest); thus, it not only complies with fiqh muamalah (Islamic commercial jurisprudence) but also contributes to community economic empowerment and improved farmer welfare. Consequently, the implementation of the qardh agreement holds potential as a Sharia-based productive financing model for the agricultural sector